A Bibliometric Review of Islamic Pedagogy in Modern Educational Systems - Judijanto, Loso; Arwen, Desri (Eastasouth Institute, 2025)
This study provides a comprehensive bibliometric review of Islamic pedagogy within modern educational systems. Through an analysis of key themes, authors, and regional trends, the research aims to map the evolving landscape of Islamic pedagogy and its intersection with contemporary educational theories and practices. The bibliometric approach identifies significant shifts in the literature, particularly the integration of sociocultural theory, the moral dimensions of education, and the role of Muslim educators in implementing Islamic educational principles. The findings reveal growing interest in the application of Islamic pedagogy in diverse geographical regions, including Indonesia, Australia, Canada, and the UAE, with a notable emphasis on adapting traditional Islamic educational practices to modern technological and multicultural contexts. The study highlights the ongoing challenges of balancing Islamic values with global educational standards and offers directions for future research, particularly in the areas of gender, multiculturalism, and the integration of technology. This review contributes to the growing body of knowledge on Islamic education and provides insights for educators, policymakers, and researchers interested in the development of Islamic pedagogy in contemporary settings.